Redescription of antarctophthirus microchir (Anoplura: Echinophthiriidae) from the South American Sea Lion, Otaria flavescens, from Patagonia, Argentina - Leonardi, María Soledad; Crespo, Enrique Alberto; Raga, Juan Antonio; Fernandez, Mercedes (Journal of Parasitology)
Antarctophthirus microchir was originally described from Phocarctos hookeri on the basis of 1 female and 1 male only. We redescribe adults and describe, for the first time, the 3 nymphal stages from specimens collected from Otaria flavescens from Patagonia, using light and scanning electron microscopy. The present material can be distinguished from other Antarctophthirus species by the presence of a fringe of setae on the back of the head, only present in Antarctophthirus trichechi and Antarctophthirus callorhini. However, A. trichechi also possess a prominent proboscis with large hooks, and A. callorhini presents less abundant and nonuniform abdominal scales in shape and size. Other differential features of A. microchir are the pattern of ovoid and uniform scales and longitudinal grooves in the surface of spines. Nymphal stage 1 differs from 2 and 3 mainly by the absence of scales and thorax without ventral spines or hairs. Nymphal stages 2 and 3 may be distinguished by the disposition of the occipital apophyses. Antarctophthirus microchir has been reported from 5 sea lion species from both hemispheres. Considering the conservative morphology, and ecological and evolutionary features of sucking lice, we raise the question of whether A. microchir from different sea lion hosts may represent a complex of cryptic species. Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Raga, Juan Antonio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Fernandez, Mercedes. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Valencia; España